Methods and Tools of Economic Education in Preschool Children (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In order to write an article about methods and means of economic education for preschool children, first of all, it is necessary to study theoretical knowledge about economic education of children. Later, practical training should be organized to develop their knowledge of economic knowledge. The article provides an explanation of these issues and recommendations for their further development. Economic education is very important for children because it determines their future life and affects their economic development. Therefore, it is very important to introduce them to economic knowledge from a young age and to educate them about this knowledge.